Antioxidant Properties of Plant Extracts: an EPR and DFT Comparative Study of the Reaction with DPPH, TEMPOL and Spin Trap DMPO - dos Santos, Adevailton Bernardo; Siqueira Silva, Dulce Helena [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Santos, Luciana Avila [UNESP]; Schmidt, Tome Mauro; Baffa, Oswaldo (Soc Brasileira Quimica, 2009)
This work presents a comparative study of the antioxidant activity of extracts from nine plant species belonging to the Brazilian flora - Swartzia langsdorffii, Machaerium villosum, Pterogyne nitens, Pera glabrata, Aegiphyla sellowiana, Copaifera langsdorffii, Chrysophyllum inornatum, Iryanthera juruensis, Didymopanax venosum - acting on the free-radicals DPPH (2,2-diphenyl-1-pierylhydrazyl) and TEMPOL (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinyloxy-1-oxyl) by electron paramagnetic resonance (EPR), and acting on the hydroxyl radical (OH circle) by the spin-trapping technique generated by a Fenton reaction. Results showed that the extracts of Iryanthera juruensis and Chrysophyllum inornatum display the strongest antioxidant activities. The results of scavenging tests were clarified by computational calculations - density functional theory (DFT), local density approximation (LDA) with SIESTA code - indicating that the energy released in the reduction reaction of TEMPOL is less than DPPH. Due to its availability and cost DPPH is more often used in these tests than TEMPOL, however TEMPOL should be considered when studying processes dealing with smaller energies.
Keywords: EPR; TEMPOL; DPPH; DMPO; DFT